2018
DOI: 10.1108/ijhcqa-09-2017-0164
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous fluid delivery time improvement: application of cross-docking system

Abstract: Purpose The cost of pharmaceutical supply chain due to drug waste is one of the current major issues in health care. Drug waste associated with intravenous (IV) fluid form of medication is one of the crucial issues for many pharmacies. The purpose of this paper is to apply a cross-docking model to minimize the IV delivery lead time to reduce drug waste by scheduling staff in a local hospital’s inpatient pharmacy. Design/methodology/approach A mixed integer linear programming model is applied to the IV delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Policy implications relate to the way in which policies may improve various elements of cross-docking, including scheduling, warehousing, and logistics operations, and support the improved distribution of goods. The implementation of an adaptive policy instead of a fixed stock policy, in line with the findings of Khorasani et al [19], is better placed to allow for cost savings in cross-docking situations. Inventory ordering policy, a key opportunity to gain efficiencies in cross-docking [72], suggest that replenishment policies are key to gaining time and cost improvements with cross-docking.…”
Section: Implications and Conclusionmentioning
confidence: 70%
See 2 more Smart Citations
“…Policy implications relate to the way in which policies may improve various elements of cross-docking, including scheduling, warehousing, and logistics operations, and support the improved distribution of goods. The implementation of an adaptive policy instead of a fixed stock policy, in line with the findings of Khorasani et al [19], is better placed to allow for cost savings in cross-docking situations. Inventory ordering policy, a key opportunity to gain efficiencies in cross-docking [72], suggest that replenishment policies are key to gaining time and cost improvements with cross-docking.…”
Section: Implications and Conclusionmentioning
confidence: 70%
“…In 1992, Wal-Mart was the most profitable retailer globally due to applying cross-docking on 85% of its inventory, which also contributed to a 2-3% cost saving [1]. The cross-docking approach is also practised in the pharmaceutical supply chain to manage speed to market and pharma waste through better scheduling and improving medication room response time and eliminating unnecessary activities [19]. Khorasani et al (2018) reported that cross-docking is efficient for moving numerous items within short periods of time [19].…”
Section: Advantages and Applications Of Cross-dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…If there does not exist an outbound truck in the outbound door, the product moves from the selected inbound truck to the temporary storage only if its current capacity is still less than its maximum capacity. This mechanism is formalized by using (15). This process is also formalized in algorithm 3.…”
Section: Proposed Modelmentioning
confidence: 99%